Molecular docking and dynamics study to explore phytochemical ligand molecules against the main protease of SARS-CoV-2 from extensive phytochemical datasets. Issue 10 (3rd October 2021) - Mahmud, Shafi; Mita, Mohasana Akter; Biswas, Suvro; Paul, Gobindo Kumar; Promi, Maria Meha; Afrose, Shamima; Hasan, Robiul; Shimu, Sharmin Sultana; Zaman, Shahriar; Uddin, Salah; Tallei, Trina Ekawati; Emran, Talha Bin; et al.
ABSTRACT: Background: The high transmission and pathogenicity of SARS-CoV-2 has led to a pandemic that has halted the world's economy and health. The newly evolved strains and scarcity of vaccines has worsened the situation. The main protease (M pro ) of SARS-CoV-2 can act as a potential target due to its role in viral replication and conservation level. Methods: In this study, we have enlisted more than 1100 phytochemicals from Asian plants based on deep literature mining. The compounds library was screened against the M pro of SARS-CoV-2. Results: The selected three ligands, Flemichin, Delta-Oleanolic acid, and Emodin 1-O-beta-D-glucoside had a binding energy of −8.9, −8.9, −8.7 KJ/mol respectively. The compounds bind to the active groove of the main protease at; Cys145, Glu166, His41, Met49, Pro168, Met165, Gln189. The multiple descriptors from the simulation study; root mean square deviation, root mean square fluctuation, radius of gyration, hydrogen bond, solvent accessible surface area confirms the stable nature of the protein-ligand complexes. Furthermore, post-md analysis confirms the rigidness in the docked poses over the simulation trajectories. Conclusions: Our combinatorial drug design approaches may help researchers to identify suitable drug candidates against SARS-CoV-2.